Lowering relative humidity level increases epidermal protein deimination and drives human filaggrin breakdown. Issue 2 (May 2017) - Cau, Laura; Pendaries, Valérie; Lhuillier, Emeline; Thompson, Paul R.; Serre, Guy; Takahara, Hidenari; Méchin, Marie-Claire; Simon, Michel
Highlights: Filaggrin is a key protein in the epidermal barrier function. Filaggrin degradation in the upper epidermis is controlled by the environmental humidity level. A deimination increase is necessary and sufficient to trigger filaggrin breakdown. The higher requisite for filaggrin degradation in dry conditions may explain the negative effects of dry and cold climate on the skin of atopic dermatitis patients. Abstract: Background: Deimination (also known as citrullination), the conversion of arginine in a protein to citrulline, is catalyzed by a family of enzymes called peptidylarginine deiminases (PADs). Three PADs are expressed in the epidermis, one of their targets being filaggrin. Filaggrin plays a central role in atopic dermatitis and is a key protein for the epidermal barrier. It aggregates keratins and is cross-linked to cornified envelopes. Following its deimination, it is totally degraded to release free amino acids, contributing to the natural moisturizing factor (NMF). The mechanisms controlling this multistep catabolism in human are unknown. Objective: To test whether external humidity plays a role, and investigate the molecular mechanisms involved. Methods: Specimens of reconstructed human epidermis (RHEs) produced in humid or dry conditions (>95% or 30–50% relative humidity) were compared. Results: RHEs produced in the dry condition presented structural changes, including a thicker stratum corneum and a larger amount of keratohyalin granules. The transepidermal water loss and the stratum corneum pH were decreased whereas the quantity of NMF was greater. This highly suggested that filaggrin proteolysis was up-regulated. The expression/activity of the proteases involved in filaggrin breakdown did not increase while PAD1 expression and the deimination rate of proteins, including filaggrin, were drastically enhanced. Partial inhibition of PADs with Cl-amidine reversed the effect of dryness on filaggrin breakdown. Conclusion: These results demonstrate the importance of external humidity in the control of human filaggrin metabolism, and suggest that deimination plays a major role in this regulation.